Efficacy of augmentation of cognitive behavioral therapy with transcranial direct current stimulation for depression: a randomized clinical trial : original investigation - Aust, Sabine; Brakemeier, Eva-Lotta; Spies, Jan; Herrera-Melendez, Ana Lucia; Kaiser, Tim; Fallgatter, Andreas; Plewnia, Christian; Mayer, Sarah V.; Dechantsreiter, Esther; Burkhardt, Gerrit; Strauß, Maria; Mauche, Nicole; et al. (JAMA psychiatry, 2022)
Major depressive disorder (MDD) affects approximately 10% of the population globally. Approximately 20% to 30% of patients with MDD do not sufficiently respond to standard treatment. Therefore, there is a need to develop more effective treatment strategies.To investigate whether the efficacy of cognitive behavioral therapy (CBT) for the treatment of MDD can be enhanced by concurrent transcranial direct current stimulation (tDCS).The double-blind, placebo-controlled randomized clinical trial PsychotherapyPlus was conducted at 6 university hospitals across Germany. Enrollment took place between June 2, 2016, and March 10, 2020; follow-up was completed August 27, 2020. Adults aged 20 to 65 years with a single or recurrent depressive episode were eligible. They were either not receiving medication or were receiving a stable regimen of antidepressant medication (selective serotonin reuptake inhibitor and/or mirtazapine). A total of 148 women and men underwent randomization: 53 individuals were assigned to CBT alone (group 0), 48 to CBT plus tDCS (group 1), and 47 to CBT plus sham-tDCS (group 2).Participants attended a 6-week group intervention comprising 12 sessions of CBT. If assigned, tDCS was applied simultaneously. Active tDCS included stimulation with an intensity of 2 mA for 30 minutes (anode over F3, cathode over F4).The primary outcome was the change in Montgomery-Åsberg Depression Rating Scale (MADRS) score from baseline to posttreatment in the intention-to-treat sample. Scores of 0 to 6 indicate no depression; 7 to 19, mild depression; 20 to 34, moderate depression; and 34 and higher, severe depression.A total of 148 patients (89 women, 59 men; mean [SD] age, 41.1 [13.7] years; MADRS score at baseline, 23.0 [6.4]) were randomized. Of these, 126 patients (mean [SD] age, 41.5 [14.0] years; MADRS score at baseline, 23.0 [6.3]) completed the study. In each of the intervention groups, intervention was able to reduce MADRS scores by a mean of 6.5 points (95% CI, 3.82-9.14 points). The Cohen d value was -0.90 (95% CI, -1.43 to -0.50), indicating a significant effect over time. However, there was no significant effect of group and no significant interaction of group × time, indicating the estimated additive effects were not statistically significant. There were no severe adverse events throughout the whole trial, and there were no significant differences of self-reported adverse effects during and after stimulation between groups 1 and 2.Based on MADRS score changes, this trial did not indicate superior efficacy of tDCS-enhanced CBT compared with 2 CBT control conditions. The study confirmed that concurrent group CBT and tDCS is safe and feasible. However, additional research on mechanisms of neuromodulation to complement CBT and other behavioral interventions is needed.ClinicalTrials.gov Identifier: NCT02633449
Gesehen am 08.01.2024